Big Bad Detective Agency - Hale, Bruce (Scholatistic Press, 2015)
"The houses of all Three (not-so-) Little Pigs were broken into and ransacked, and the Pigs are squealing for justice. So Prince Tyrone, ruler of Fairylandia, drags in the obvious suspect: Wolfgang. The lone wolf has big teeth, sharp claws, no alibi -- and a single day to find the real culprit and clear his big bad name. When Wolf (reluctantly) teams up with the fourth Little Pig to crack the case, the Big Bad Detective Agency -- and an adventure way funnier than your average fairy tale -- is born!"--